PENGARUH EFISIENSI OPERASI, RISIKO PEMBIAYAAN DAN RISIKO LIKUIDITAS TERHADAP PROFITABILITAS ( Studi Pada Bank Umum Syariah Yang Terdaftar Di Otoritas Jasa Keuangan) - Fathoni, Rizal Hisyam (Jurnal Ilmiah Mahasiswa FEB, 2020)
This study aims to examine and analyze the effect of operating efficiency, financing risk, and liquidity risk to the profitability of Sharia Commercial Banks that are listed on the Financial Services Authority the period 2016 - 2018. This research is explanatory research. The type of data in this research is quantitative data and methods of data collection is documentation. Samples were taken using a purposive sampling method. The population in this research is all of Islamic banking which are listed on the Financial Services Authority in the 2016-2018 period. From a population of 34 Islamic banking, 12 Islamic banking was obtained as a sample with a period of 3 years (2016-2018). Data were analyzed using multiple linear regression analysis. Based on the results of data analysis concluded that the risk of financing gives no significant effect on profitability. While operating efficiency and liquidity risk have a significant positive effect on profitability. Based on the results of data analysis concluded that financing risks have an influence not significantly to profitability. Whereas efficiency operation and risk liquidity having a positive significant impact on profitability. Based on the results of the F-test, it can be concluded that efficiency operation, financing risks, and risks liquidity simultaneously have a significant effect on profitability in the general sharia-based bank in Indonesia that listed on Financial Services Authority the period 2016-2018.Keywords: Profitability, Operating Efficiency, Non-Performing Financing, Liquidity Risk